Enhanced energy absorption of high intensity laser pulses by targets of modulated surface - Cerchez, Mirela; Swantusch, M.; Toncian, M.; Zhu, X. M.; Prasad, R.; Toncian, T.; Roedel, Ch.; Jaeckel, O.; Paulus, Gerhard G.; Andreev, A. A.; Willi, Oswald (Applied Physics Letters, 2018)
Investigations of energy transfer of high intensity (I = 5 × 1019 W/cm2), ultrashort (<30 fs) Ti:Sa laser pulses to solid targets with a randomly rough surface have been performed. We investigated the influence of the target surface morphology on the efficiency of energy transfer of p- polarized laser pulses characterized by a very high contrast. Targets with a roughness σ larger than ∼20% of the laser wavelength proved to absorb a remarkably large fraction of energy reaching up to 70%, almost independent of the incidence angle. Numerical simulations of various interaction conditions are in agreement with the experimental data and confirm the effect of the target morphology and its surface parameters on the enhanced energy absorbed fraction.
CRIS-Team Scopus Importer:2023-04-20